The Underlying Osseous Deformity in Plantar Plate Tears: A Radiographic Analysis. Issue 2 (April 2013) - Klein, Erin E.; Weil, Lowell; Weil, Lowell Scott; Knight, Jessica
Purpose . Plantar plate tears can cause pain and deformity of the forefoot. The purpose of this study is to correlate common radiographic findings with observed intra-operative pathology in patients with plantar plate pathology. Methods. Bilateral weight-bearing radiographs were reviewed for 88 patients (106 feet) who underwent surgical repair of suspected plantar plate pathology. Parameters reviewed included the first intermetatarsal angle, the metatarsus adductus angle, the second and third metatarsophalangeal angles, splaying of the second and third toes, evaluation of the metatarsal parabola by 3 different methods, the first and second lateral declination angles, and the second lateral metatarsophalangeal angle. Results. Of 106 feet, 97 had intra-operative plantar plate tears. The radiographs of patients with plantar plate tears had an increased amount of digital splay on the anteroposterior radiograph compared to patients without pathology. For patients with unilateral plantar plate pathology, the metatarsal parabola of the symptomatic foot was compared with that of the asymptomatic foot. A significantly increased second metatarsal protrusion distance as measured by 2 different methods was noted in the symptomatic foot. Odds ratios revealed that patients with an intermetatarsal angle >12, medial deviation of the second toe, and splaying of the digits were more likely to be diagnosed with a plantar plate tear intra-operatively. Conclusion. Although radiographs do not definitively diagnose plantar plate tears, understanding osseous forefoot architecture will aid with diagnosis in the absence of other osseous pathology. Furthermore, these data suggest that parabola should be corrected to maintain long-term correction of plantar plate pathology. Level of Evidence: Prognostic, Level II